PENERAPAN MODEL BAMBOO DANCING TERHADAP KEMAMPUAN BERHITUNG MATERI FPB DAN KPK - Dwi Novita Sari; Ali Shodiqin; Filia Prima Artharina (Universitas Negeri Medan, 2019)
Abstract: Implementation of Bamboo Dancing Model on the Ability to Calculate FPB and KPK Materials. In this study, the objective to be achieved is to know the students' ability to count using the learning model of bamboo dancing with the help of pastar media better than conventional learning of FPB material and Class IV KPK at SDN Kalicari 01 and know whether there is an effect of active attitude on the application of bamboo dancing learner model assisted by pastar media on the ability to calculate FPB material and grade IV KPK at SDN Kalicari 01. This study uses a quantitative approach. Samples taken were 24 students from class IVA and IVB. The results of his research are based on the hypothesis test 1 by using the t test it was found that students' ability to count using the Bamboo Dancing model assisted by PASTAR media was better than conventional learning of FPB and KPK material in grade IV SDN Kalicari 01. While based on the Hypothesis 2 test using the regression equation test and test simple regression coefficient, it can be said that there is an influence of active attitude on the application of bamboo dancing learner model assisted by pastar media on the ability to calculate FPB and KPK grade IV material at SDN Kalicari 01.Keywords: Models bamboo dancing, FPB and KPK, Ability to countAbstrak: Penerapan Model Bamboo Dancing Terhadap Kemampuan Berhitung Materi FPB dan KPK. Tujuan penelitian ini adalah untuk mengetahui kemampuan berhitung siswa dengan menggunakan model pembelajaran bamboo dancing berbantu media pastar lebih baik dari pembelajaran konvensional materi FPB dan KPK kelas IV di SDN Kalicari 01 serta mengetahui adakah pengaruh sikap keaktifan pada penerapan model pembelajar bamboo dancing berbantu media pastar terhadap kemampuan berhitung materi FPB dan KPK kelas IV di SDN Kalicari 01. Penelitian ini menggunakan pendekatan kuantitatif. Sampel yang diambil adalah masung-masing 24 siswa dari kelas IVA dan IVB. Hasil penelitiannya adalah Berdasarkan uji hipotesis 1 dengan menggunakna uji t didapatkan kemampuan berhitung siswa dengan menggunakan model Bamboo Dancing berbantu media PASTAR lebih baik dari pembelajaran konvensional materi FPB dan KPK di kelas IV SDN Kalicari 01. Sedangkan Berdasarkan Uji hipotesis 2 menggunakan uji persamaan regresi dan uji koefesien regresi sederhana maka dapat dikatakan bahwa ada pengaruh sikap keaktifan pada penerapan model pembelajar bamboo dancing berbantu media pastar terhadap kemampuan berhitung materi FPB dan KPK kelas IV di SDN Kalicari 01.Kata Kunci: Model bamboo dancing, FPB dan KPK, Kemampuan berhitung.